TANGGUNG JAWAB SOSIAL PERUSAHAAN DAN PEMBERDAYAAN MASYARAKAT SEKITAR PERUSAHAAN - Henny Ekawati (Populasi, 2007)
Bussiness practice lately had caused many damages to the society around the corporates. They were directly effected by this practice in a bad way. They still live poorly while the corporates were getting richer by absorbing as much as they could from the resources. The policy by the goverment is to make the corporates giving back what they had taken to the society around them. They should arrange programs namely Corporate Social Responsibilites to empower the society. But in the implementation, some problems occured, such as the inconsistency of the program and the top-down program which did not involved society and related institutions. Later the program should be studied more to at the end empower the society and minimalized conflicts. Bussiness practice lately had caused many damages to the society around the corporates. They were directly effected by this practice in a bad way. They still live poorly while the corporates were getting richer by absorbing as much as they could from the resources. The policy by the goverment is to make the corporates giving back what they had taken to the society around them. They should arrange programs namely Corporate Social Responsibilites to empower the society. But in the implementation, some problems occured, such as the inconsistency of the program and the top-down program which did not involved society and related institutions. Later the program should be studied more to at the end empower the society and minimalized conflicts.